Information System for State-owned inventories Management at the Faculty of Computer Science - Tjahjanto, Tjahjanto; Arista, Artika; Ermatita, Ermatita (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Information technology development brings a very broad impact on human life. With this Model View Controller (MVC) concept, information system development could be developed in accordance needs of the user’s information system development and be able to adapt the development in the organization. Needs of fast and precise and adaptive information system information is needed in this modern era when everything needs to be fast. Faculty of computer science (FIK) Universitas Pembangunan Nasional Veterans Jakarta (UPNVJ) as one work unit under the government agency, has State-owned inventories to support all activities to carry out the Tri Dharma or the higher education pillars, especially in the field of education. The state-owned inventories or devices are available in FIK such as monitors, printers, LCD, mouse, etc. For continuity of this educational process, the state-owned inventories must be maintained. Therefore, in this research, the researchers will develop an information system to document the state-owned inventory records for helping the management of the state-owned inventories in the faculty of computer science at UPN Veteran Jakarta. The information system was built using the waterfall method and using the PHP programming language and MySQL database running on a server. This information system provides features to manage users, manage components, access system logs, access system settings, manage devices, manage the location, and access reports. The system that has been developed has also passed the eligibility assessment for all aspects of both visual communication aspects, software engineering aspects, and usability aspects.